Mosquito larvicidal and cytotoxic potentials of the different extracts of the aerial part of Blepharis ciliaris (Acanthaceae) against Culex pipiens (Diptera: Culicidae) - Almekhlafi, Fahd; Almohssin , Abdulrahman Zaid M.; Abutaha, Nael; Al-Qahtni, Abdulmani H.; Wadaan, Mohammed A.; Al-Khalifa, Mohammed S. (Revista Colombiana de Entomología, 2024)
This study explores the larvicidal potential of a hexane extract from Blepharis ciliaris against Culex pipiens mosquitoes, a known vector of various diseases. The study aimed to find an eco-friendly alternative to chemical insecticides. Promising results were obtained, with the extract showing significant larvicidal activity. The LC50, LC90, and LC95 values against C. pipiens were determined as 125.53, 190.5, and 198.76 µg/mL, respectively. Furthermore, histological observations using a light microscope revealed notable changes in the midgut structure of the treated larvae, including degradation of microvilli, degeneration, and protrusion of epithelial cells and peritrophic membrane, loss of nuclei, and irregular microvilli. These findings suggest that the hexane extract from B. ciliaris has the potential as a natural larvicidal agent against C. pipiens mosquitoes. The MTT assay results indicate that the tested extracts did not exhibit cytotoxic effects on Huh-7 cells, and no morphological changes were observed under light microscopy. The findings of this study suggest that B. ciliaris contains bioactive compounds that could serve as potential bio-larvicides for controlling C. pipiens vectors. Further research should be conducted to assess the efficacy of using this botanical insecticide in small-scale field trials to develop environmentally safe interventions for controlling C. pipiens populations.